Pengembangan Kawasan Wisata pada Rest Area Boja dalam Mendukung Peningkatan Pedapatan Desa Melalui Perilaku Herding (Studi Kasus di Kawasan Wisata Rest Area Desa Boja, Kecamatan Boja, Kabupaten Kendal) - Yuyun Ristianawati; Prihasantyo Siswo Nugroho; Kiswoyo (Future Science, 2021)
The aims of this research is to study the mindset of Herding's behavior on the income level of tourism objects through the results of tourism development in the Rest Area of Boja Kendal Village. In this study, 95 people/MSMEs. In this study, the authors used a purposive random sampling technique. The results of this study are herding behavior has a positive and significant effect on the income level of MSMEs in the Boja rest area tourist attraction. Herding behavior has no effect on tourism development decisions. The development of tourism objects has no effect on increasing income. Herding behavior has no significant effect on the income level of tourist objects through tourism area development decisions. So that the development of tourist areas is not able to mediate the influence of herding behavior on increasing MSME income in the Boja rest area tourist attraction.